SYNERGISTIC EFFECT OF PHEROMONES AND CITRUS PLANT EXTRACTS AGAINST BACTROCERA ZONATA TITTLE SYNERGISTIC EFFECT (Journal of Medical & Health Sciences Review, 2025)
The fruit fly, Bactrocera zonata is found infesting more than 50 cultivated and wild fruit species and thus responsible for 25-100% of damages in fleshy fruits Pheromone and para-pheromone traps are used to examine the population extent of fruit flies in different locations of the world. Therefore, the present research was conducted to assess the synergistic effect of pheromones and citrus plant extracts. The experiment was performed in Y-tube olfactometer in laboratory conditions to observe the attraction/or repellence of B. zonata towards pheromones and citrus plant extracts separately and in combination. The study was conducted in Vector Ecology Laboratory, Department of Entomology, University of Agriculture, and Faisalabad. For odor preference, about six female peach fruit flies was released in a free choice wind tunnel containing host fruit. The relative attraction percentage toward each fruit was determined on the basis of total number of flies attracted to each host fruit and the process was repeated three times with one hour interval. To observe oviposition preferences about 20 male and female fruit flies adult of 14-21 days old and 24-48 hour starved was released in rearing cages (60 × 30 × 30 cm) for 24h with 250 g of each fruit. Host preference was evaluated on the basis of total number of pupae and emergence of adults from each fruit. The mean attraction and repellence behavior was analyzed using analysis of variance (ANOVA) and the Tuckey HSD test.